Knowledge and Perception of the Population About the Effect of Iodine Deficiency in Riyadh Region, Saudi Arabia - Mohammad S. Ahmad; Waleed H. Alkhalidi; Abdulrahman A. Alhassan; Osama M. Alshabanat; Khaled M. Aldhafiri; Abdullah A. Alfahad; Nawaf Y. Sharahili (Journal of Pharmacy and Bioallied Sciences)
Objective: To assess the knowledge and perception of the population about the effect of iodine deficiency in Riyadh region, Saudi Arabia. Methodology: Descriptive cross-sectional study conducted at Riyadh region Saudi Arabia. Simple random sampling was considered in this study and 202 participants were selected. Data was collected by a pre-tested questionnaire after obtaining ethics approval Data was analyzed by SPSS version 25. Results: The findings revealed the knowledge about iodine deficiency is high, particularly among younger individuals (P = 0.049), while significant gaps remain in understanding its severe implications. The highest population who had knowledge and awareness about iodine deficiency was found at age 20–29 (60.39%) and the lowest at age >60 (20%). The highest population that has associations between the problems and diseases that the people might suffer from in iodine deficiency was found at age 15–19 (14.81%) and the lowest at age 20–29 (86.14%). Conclusion: While the findings reveal a high level of awareness regarding iodine deficiency, particularly among younger individuals, significant knowledge gaps persist regarding its severe implications, especially among older age groups. Despite these disparities, perceptions regarding iodine’s impact on bone health remain consistent across genders, ages, educational backgrounds, and marital statuses.